Harnessing the potential of selected bio-agents for sustainable management of plant parasitic nematodes in coffee - Anyango, O.C. (2024)
East Africa confronts multiple challenges in coffee production, including aging plantations, subpar inputs, climate change, and pest-related issues. Among these threats, plant parasitic nematodes (PPN) pose a significant concern, contributing to estimated global losses of up to 15% in coffee production. Despite their impact, PPN often remain overlooked or underestimated as a major factor causing damage to coffee crops. In Kenya, specific symptoms of PPN damage are poorly understood, leading to their gradual manifestation over years and resulting in enduring losses to the industry. Biocontrol has been explored in management of PPN on other crops like horticultural, ornamental and other annual crops but has not been registered in coffee, a perennial crop. This study aimed to assess the potential of microbial antagonists in suppressing PPN and improving coffee production in Kenya. The effectiveness of three biocontrol agents namely Trichoderma asperellum, Purpureocillium lilacinum, and Bacillus subtiliswas evaluated under pot and field conditions, targeting Meloidogyne hapla, a prevalent nematode species affecting coffee in the Ruiru region of Kenya. In pot experiment, nematode-infested soil and roots from Chania Coffee Farm was utilized. Three Biocontrol agents, namely Bacillus subtilis, Trichoderma asperellum and Purpureocilium lilacinum were tested. Each of biocontrol agent was administered at three different rates: 6.67 × 103, 6.67 × 104, and 6.67 × 105 spores/ml, using a randomized complete block design with 20 treatments and five replicates. Drenching with 150 ml of the biocontrol agent occurred every two weeks for six months after transplanting, with assessments conducted at the experiment's termination. Two biocontrol agents, Trichoderma asperellum and Purpureocilium lilacinum, were tested in the field experiment. The recommended dose for other annual crops, 2 × 107 spores/ml, was applied in seven fields, each with three treatments and four replicates, spanning for two years. Drenching each plant with 40 ml of the respective product in 20 liters of water was done monthly after subsequent soil sampling. Monthly activities included soil sampling, nematode extraction, quantification, and identification, as well as fungal re-isolation. The nematode survey revealed ten genera of plant parasitic nematodes; Meloidogyne spp., Tylenchorhynchus spp., Helicotylenchus spp., Longidorus spp., Pratylenchus spp., Trichodorus spp., Scutellonema spp., Rotylenchulus spp., Paratylenchus spp., and Hemicycliophora spp., with varying densities based on coffee cultivar. Ruiru 11 exhibited a lower mean density of PPN, with 40, as compared to cv French Mission, which recorded 62, with the control group having 43 nematodes per 100cc of soil and 5 g of roots. Similarly, Ruiru 11 had a lower count of free-living nematodes, with 276, compared to cv French Mission, which recorded 326 nematodes per 100cc of soil and 5 g of roots. Trichoderma asperellum significantly colonized coffee roots with 2.45 × 106 cfu/g of soil and roots, a higher count compared to P. lilacinum, which recorded 3.22 × 103 cfu/g of soil and roots. In cv Ruiru 11, the percentage mean of PPN recorded per treatment was significant, with the untreated group having 36.7%, P. lilacinum 32.5%, and T. asperellum 30.8%. The study suggests that older plants associated with French Mission may contribute to this difference. Pot experiment results indicated a significant reduction in M. hapla on coffee with all bio-control agents at spore concentrations of 6.67 × 104 spores/ml and 6.67 × 105 spores/ml. Coffee cultivar Ruiru 11 exhibited higher efficacy in biocontrol agent uptake, resulting in a lower root galling index compared to French Mission. However, the galling index showed no significant variation among the bio-control agents. Trichoderma, at a spore concentration of 6.67 × 105 spores/ml, significantly reduced M. hapla densities in plant roots compared to P. lilacinum at a similar concentration. Additionally, the study demonstrated increased plant biomass in plants treated with biocontrol agents. This study recommends use of B. subtilis, T. asperellum, and P. lilacinum at a spore concentration of 6.67 × 104 spores/ml to effectively manage plant parasitic nematodes in coffee plantations. Further research should explore the use of different coffee cultivars and determine the optimal stage for exposing coffee to biocontrol agents. Additionally, there is a need to investigate the integration of these biocontrol agents into existing control practices for more effective and sustainable nematode management.